From invisibility to empathy: a study of homophobia in China and Taiwan - Lazzara, Emmanuele (2019)
This thesis explores how homophobia is manifested, produced, and perpetuated in Chinese and Taiwanese society, and what strategies are adopted to resist and disrupt discriminatory patterns. I deliberately shift the focus from overt homophobia to more subtle manifestations, since my data demonstrates that the latter are mostly affecting the research participants. The data was collected primarily through in-depth qualitative interviews and focus groups and supported by observation in the field. The participants are both PASS (people attracted to the same sex) and heterosexuals. I start by deconstructing the heteronormative system, since this constitutes the background against which homosexuality is denormalised. I then illustrate how PASS are marginalised through enforced invisibility and othering. Despite sharing common roots, Chinese and Taiwanese homophobia manifests in different ways and to different degrees mainly due to different political contexts and diverging cultural values of collectivism and individualism.